Improving Women's Mental Health during a Pandemic - Michael Vlassopoulos; Abu Siddique; Tabassum Rahman; Debayan Pakrashi; Asad Islam; Firoz Ahmed (Institute of Labor Economics (IZA), 2021)
In low-income settings, women are vulnerable to the psychological distress caused by the social and economic impact of large-scale shocks (e.g., pandemics, natural disasters, political). This paper evaluates a randomized over-the-phone counseling intervention aimed at mitigating the mental health impact of COVID-19 on a sample of 2,402 women across 357 villages in Bangladesh. We find that the provision of mental support to participating women improves their mental health ten months post-intervention, leading to reductions of 20.4% in the prevalence of moderate and severe stress and 32.8% in depression, relative to women in the control group. We also find positive impacts on economic outcomes: household food security and time invested in homeschooling of children, suggesting that improvement in mental health is an important step toward better economic well-being for these women. Finally, we also observe impacts on various other outcomes, including preventive health behavior associated with COVID-19 and vaccination take-up. Our results suggest that this type of low-cost intervention can be effective in providing rapid psychological support to vulnerable groups in times of crises.
Keywords: I10; I12; I18; I31; O12; 330; mental health; COVID-19; food security; telecounseling; randomized experiment; parental investment; rural Bangladesh